1999
DOI: 10.1152/ajprenal.1999.276.3.f347
|View full text |Cite
|
Sign up to set email alerts
|

Isoforms of the Na-K-2Cl cotransporter in murine TAL I. Molecular characterization and intrarenal localization

Abstract: We have identified several alternatively spliced cDNAs encoding mBSC1, an apical bumetanide-sensitive Na+-K+-2Cl−cotransporter from mouse kidney. Two full-length clones were isolated, designated C4 and C9, predicting proteins of 770 and 1,095 amino acids, respectively. The C4 isoforms are generated by utilization of an alternative polyadenylation site located within the intron between exons 16 and 17 of the mBSC1 gene on chromosome 2; the resultant transcripts predict a truncated COOH terminus ending in a uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 26 publications
0
88
0
Order By: Relevance
“…It has been previously shown that ammonium transport and the expression of ROMK1, an NKCC2 splice variant, and cldn19 are heterogeneous in the TAL (19,(35)(36)(37). The first description of different TAL cell types was in 1967 by Allen and Tisher (38), who discovered two cell types in rat TAL by means of scanning electron microscopy: R (rough) cells with prominent microvilli and extensive lateral interdigitations and S (smooth) cells generally devoid of extensive microvilli and with less complex lateral interdigitations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that ammonium transport and the expression of ROMK1, an NKCC2 splice variant, and cldn19 are heterogeneous in the TAL (19,(35)(36)(37). The first description of different TAL cell types was in 1967 by Allen and Tisher (38), who discovered two cell types in rat TAL by means of scanning electron microscopy: R (rough) cells with prominent microvilli and extensive lateral interdigitations and S (smooth) cells generally devoid of extensive microvilli and with less complex lateral interdigitations.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, identifying proteins that interact with the C-terminal tail of NKCC2 should help to determine the mechanism of regulated NKCC2 trafficking. With regard to the NKCC2 C terminus, it has been reported that the murine renal specific Na-K-2Cl co-transporter gene Slc12A1 exhibits two spliced isoform products that differ at the C terminus (30). However, the full-length isoform (L-NKCC2) appears to be, functionally, the main renal Na-K-Cl co-transporter that provides the apical pathway for vasopressin-regulated NaCl transport across the TAL (69 -71).…”
Section: Discussionmentioning
confidence: 99%
“…A negative RT-PCR was performed with H 2 O as a replacement of superscript II. For PCR, 2 l of the cDNA solution was supplemented with 5 l of 10ϫ PCR buffer, 1 l of 50 mM MgCl 2 , 10 pmol of each primer, 1 l of a 10 mM dNTP solution, and 1.25 units of Taq polymerase in a final volume of 50 l. The sequence of the used primers to amplify full-length mouse aldolase B and NKCC2 cDNAs were 5Ј-gaggactcttcccctttgct-3Ј (sense) and 5Ј-ataggtgtaggaggctgtga-3Ј (reverse) for aldolase, and 5Ј-atgtcggtcagcatcccttcc-3Ј (sense) and 5Ј-ttaagagtaaaatgttaagac-3Ј (reverse) for NKCC2 (30). Samples were denatured at 95°C for 4 min, followed by 35 cycles of 95°C for 1 min, 58°C for 1 min, and 72°C for 1.5 min.…”
Section: Total Rna Extraction Reverse Transcription Conventional Rtmentioning
confidence: 99%
“…However, two examples of naturally occurring dominant negative CCCs have been reported. The first is the inactive C4 variants of mouse NKCC2, the shorter of two NKCC2 C-terminal polypeptide variants (30,31). Co-expression of inactive C4 polypeptide (A4) with the longer and functionally active but cAMP-insensitive C9 variant of NKCC2 (F9) inhibited its cation transport activity in a manner that was partially reversed by cAMP-isobutylmethylxanthine (31).…”
Section: Figmentioning
confidence: 99%